Capital Structure and Firm Value of Sri Lankan Listed Companies - Koperunthevy, K. (National center for advanced studies in humanities and social science Sri Lanka., 2018)
The objective of financial management (FM) is to maximize the firm value and FM involves several finance related decisions. Capital structure is one of the financial decisions and this decision determines the mix of debt and equity capital. Theories related to capital structure are developed based on some assumptions. Therefore, the impact of capital structure on firm value is still a debatable topic. Therefore, the main objective of this study is to identify the impact of capital structure on firm value. Based on the availability of financial reports, data were collected from 199 listed companies on Colombo Stock Exchange from 2007/08 to 2012/2013 expect Bank Finance and Insurance sectors. Debt to equity ratio (D/E ratio), Financial Leverage Multiplier (FLM) and age of the firm (natural logo of the age) were considered as independent variables and Tobin Q was used to measure firm value. Pooled, fixed effects, and random effect regression models were used to identify the impact of capital structure on firm value. The coefficient values of D/E ratio and FLM show a negative insignificant impact and age of the firm has positive significant impact on firm value. The pooled, fixed effect and random effect regression results revealed that the age is most significant variable to determine the firm value and capital structure is not a matter. Based on the Breusch Pagan LM test (p value= 0.000) the random effect model is more appropriate than pooled regression and Hausman test value (p value= 0.000) proves that fixed effect is more appropriate model than random effect model. These results confirm that the capital structure significantly did not impact on firm value. Thus, the results of this study prove that capital structure does not matter in determining the firm value.
Keywords: Capital structure; Debt equity ratio; irm value; Tobin Q